Design of Remote Desktop Invocation Based Middleware for Logistic Application - Jadied, Erwid Musthofa; Andhika, I Made; Pratama, I Putu Agus Eka; Tampubolon, Anthon R (JITTER : Jurnal Ilmiah Teknologi dan Komputer; Vol 5 No 3 (2024): JITTER, Vol.5, No.3, December 2024DO - 10.24843/JTRTI.2024.v05.i03.p10, 2025)
This paper presents a Java-based Desktop Application for Office Supplies Logistics, utilizing a Client-Server-Middleware architecture. The purpose of this research is to provide a comprehensive overview and detailed explanation of the software being developed. It is intended for use by software developers involved in the creation of the Java-based office supplies logistics application and its users, as well as other stakeholders involved in the system. This research will serve as a reference throughout the development process and as a tool for evaluation during and after the software development. By providing clear and focused guidance, this Software Requirement Spesification (SRS) aims to ensure that the software development process is well-directed and free of ambiguity, especially for the developers.